Global employer branding : Influencing talent attraction and retention for current and prospective employees - Balic, Enis (My University, 2025)
The global talent competition has intensified, making employer branding a strategic lever for attracting and retaining talent in multinational corporations. This thesis examines how a global employer brand influences perceptions of attraction and retention, clarifying the concept and its connection to corporate strategy. Guided by the social identity theory and person- organization fit theory, the study employs an interpretivist, qualitative design, utilizing semi- structured interviews with ten final year Finnish and German students all of whom had previous work experience (most had about one year, but a few up to two years) gained through internships, student jobs, traineeships, or full-time positions directly relevant to their respective disciplines. Findings indicate that global employer brands are comprising an instrumental-symbolic value proposition, credible promise-keeping systems (leadership, culture, and internal communication), and a global-local balance explicitly linked to strategic goals and KPIs (key performance indicators). Attraction is driven by faithfulness, value alignment, and honest signals during early touchpoints, with respondents highlighting crystal-clear, ethical communication over salary or role specifics. Retention hinges on fulfilling psychological contracts, providing development opportunities, offering reasonable treatment, and maintaining a sustainable work- life balance; consistent values in day-to-day practice strengthen identification and loyalty. The MNC setting both attracts (mobility, learning, prestige) and constrains (bureaucracy, depersonalization), requiring careful judgement of global and local aspects. The study contributes an integrated global employer brand view that connects brand assets to identity/fit mechanisms and to talent outcomes, and offers practical guidance: design honest, lived-value propositions; align global messaging with local realities; and measure promise-keeping through attraction/retention indicators.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business